2010
DOI: 10.1111/j.1570-7458.2009.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

How transgenic and classically bred apple genotypes affect non‐target organisms on higher trophic levels

Abstract: Current plant breeding comprises classical techniques as well as biotechnological methods suitable to insert target genes into the plant genome. Potential non-target effects of these newly developed plants have to be evaluated in appropriate risk assessment studies. We investigated non-target effects of four apple genotypes (Malus × domestica L. Borkh.; Rosaceae). They were either susceptible or resistant to the fungal phytopathogen causing apple scab, Venturia inaequalis (Cke.) Wint. (Ascomycotina: Pleosporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…Inclusion of all trees, both noninoculated and pathogeninoculated, yielded a difference in herbivore growth rate between wild-type American and Chinese chestnuts, but neither differed from the transgenic chestnut. A similar pattern was observed in another study; in the presence or absence of phytopathogens, more adults of the spotted tentiform leafminer [Phyllonorycter blancardella (F.)] emerged from a conventionally bred, fungal-resistant apple (Malus domestica Borkhausen) cultivar than from a susceptible variety, but neither differed from transgenic-susceptible and transgenic-resistant genotypes, though development times were comparable across all tree types (Vogler et al 2010). However, in our study, analysis restricted to noninoculated chestnuts found no variation in larval performance among tree types.…”
Section: Discussionsupporting
confidence: 69%
“…Inclusion of all trees, both noninoculated and pathogeninoculated, yielded a difference in herbivore growth rate between wild-type American and Chinese chestnuts, but neither differed from the transgenic chestnut. A similar pattern was observed in another study; in the presence or absence of phytopathogens, more adults of the spotted tentiform leafminer [Phyllonorycter blancardella (F.)] emerged from a conventionally bred, fungal-resistant apple (Malus domestica Borkhausen) cultivar than from a susceptible variety, but neither differed from transgenic-susceptible and transgenic-resistant genotypes, though development times were comparable across all tree types (Vogler et al 2010). However, in our study, analysis restricted to noninoculated chestnuts found no variation in larval performance among tree types.…”
Section: Discussionsupporting
confidence: 69%
“…The nontarget effects of scab-resistant GM apple tissue was tested by Vogler et al (2010). Neither the apple leafminer Phyllonorycter blancardella (Lepidoptera: Gracillariidae) nor the parasitoid wasp Pholetesor circumscriptus (Braconidae) were negatively affected.…”
Section: Direct Impact Of Transgenes On Arthropodsmentioning
confidence: 99%
“…Volatile organic compounds seem to be reliable indicators of insect herbivory (Griese et al 2017 ) and may function as infochemicals about attractiveness of plants or working as repellents. Phytochemical diversity drives plant–insect community diversity (Richards et al 2015 ), and plant/pests have to be seen as communication network (Vogler et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%